2018
DOI: 10.1002/jcb.28143
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐543 promotes ovariectomy‐induced osteoporosis through inhibition of AKT/p38 MAPK signaling pathway by targeting YAF2

Abstract: The present study aimed to determine the roles of miRNA‐543 in osteoporosis in rats induced by ovariectomy. The osteoporosis rat model was established by ovariectomy induction. MiRNA‐543 expression in osteoblasts was measured by quantitative real‐time polymerase chain reaction. The cell proliferation and apoptosis were measured by the 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide and flow cytometry assays, respectively. Western blot analysis was conducted to examine the expression of YAF‐2 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…In ovariectomized rats, overexpression of miRNA-543 was found to significantly suppress cell growth and promote apoptosis in osteoblasts [ 50 ]. In addition, miRNA-543 upregulation inhibited YAF-2 (YY1-associated factor 2) expression in osteoblasts [ 50 ]. The effects of miRNA-543 were further enhanced by YAF-2 knockdown [ 50 ].…”
Section: The Role Of Micro Rna (Mirna) and Long-non-coding Rna (Lnmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovariectomized rats, overexpression of miRNA-543 was found to significantly suppress cell growth and promote apoptosis in osteoblasts [ 50 ]. In addition, miRNA-543 upregulation inhibited YAF-2 (YY1-associated factor 2) expression in osteoblasts [ 50 ]. The effects of miRNA-543 were further enhanced by YAF-2 knockdown [ 50 ].…”
Section: The Role Of Micro Rna (Mirna) and Long-non-coding Rna (Lnmentioning
confidence: 99%
“…In addition, miRNA-543 upregulation inhibited YAF-2 (YY1-associated factor 2) expression in osteoblasts [ 50 ]. The effects of miRNA-543 were further enhanced by YAF-2 knockdown [ 50 ]. These findings suggest that inhibiting miRNA-543 could potentially protect osteoblasts against ovariectomy-induced osteoporosis through the AKT/p38 MAPK signaling pathway and targeting YAF2 [ 50 ].…”
Section: The Role Of Micro Rna (Mirna) and Long-non-coding Rna (Lnmentioning
confidence: 99%
“…Inhibiting miR-543 can protect osteoblasts by upregulating YY1-associated factor 2 (YAF2) and interfering with the AKT/p38 MAPK signaling pathway, which is beneficial to the diagnosis and treatment of osteoporosis (X. Li, Ning, Zhao, & Wan, 2018 (J. Wang, Kong, et al, 2020).…”
Section: The Role Of Mir-543 In Human Noncancerous Diseasesmentioning
confidence: 99%
“…Microribonucleic acids (microRNAs or miRs) are a type of single-stranded, non-coding and small-molecule RNAs approximately 18-25 nucleotides in length, which are involved in the occurrence and progression of various diseases (7,8). It has been reported that some miRs can participate in bone turnover, bone metabolism and bone development, thereby regulating the occurrence and progression of OP (9)(10)(11). However, whether there is a certain association between miRs and T2DM + OP has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In previous experiments, several miRNAs related to OP have been screened, and it was found that miR-205 had a certain association with T2DM + OP in elderly patients (9)(10)(11). In the present study, therefore, the expression of miR-205 in bone tissues and serum of elderly female patients with T2DM + OP was explored, and the effect of miR-205 on osteogenesis/adipogenesis of bone marrow mesenchymal stem cells (BMSCs) and its specific mechanism in elderly female mice with T2DM + OP were investigated, so as to provide new insight for the clinical treatment of elderly female patients with T2DM + OP.…”
Section: Introductionmentioning
confidence: 99%